Contribution of Implementation of Reward and Punishment as a Student Disciplinary Strategy in Completing Assignments - Irma Aprilia; Uut Septiana; Wulan Marthania; Endrise Septina Rawanoko (KOLABORASI: Journal of Multidisciplinary, 2024)
Character education needs to be implemented to protect students from the moral crisis that is rampant. The preparation of this article aims to determine the contribution of the Reward and Punishment method as a form of strategy that can foster students' disciplinary character, especially to discipline students in their assignments and behavior in class. The research method used is Literature Review through the Google Scholar database for the period 2022-2024. The Reward and Punishment Method focuses on how a teacher provides feedback on student actions, when students do positive things then the student gets a Reward or award and when students do negative things then the student gets Punishment or punishment. This method is effectively applied to foster students' disciplinary character in doing assignments while still paying attention and considering the conditions of the teacher and students in the classroom.